The CO2/CH4 Separation Potential of ZIF-8/Polysulfone Mixed Matrix Membranes at Elevated Particle Loading for Biogas Upgradation Process - Sutrisna, Putu Doddy; Hadi, Ronaldo Pangestu; Siswanto, Jonathan; Prabowo, Giovanni J (International Journal of Renewable Energy Development, 2021)
Biogas is a renewable energy that has been explored widely in Indonesia to substitute non-renewable energy. However, the presence of certain gas, such as carbon dioxide (CO2), can decrease the calorific value and generate greenhouse gas. Hence, the separation of CO2 from methane (CH4) occurs as a crucial step to improve the utilization of biogas. The separation of CH4/CO2Â can be conducted using a polymeric membrane that needs no chemical, hence considered as an environmentally friendly technique. However, the utilization of polymeric membrane in gas separation processes is hampered by the trade-off between gas throughput and selectivity. To solve this problem, the incorporation of inorganic particles, such as Zeolitic Imidazolate Framework-8 (ZIF-8) particles, into the polymer matrix to improve the gas separation performance of the membrane has been conducted recently. In this research, ZIF-8 has been incorporated into Polysulfone matrix to form ZIF-8/Polysulfone-based membrane by simple blending and phase inversion techniques in flat sheet configuration. The pure gas permeation tests showed an increase in gas permeability (26 Barrer compared to 17 Barrer) after the inclusion of ZIF-8 particles with a slight decrease in CO2/CH4selectivity for particle loading more than 15wt. %. Therefore, the membrane with 15wt. % of particles showed the best performance in terms of gas selectivity. This result was due to the aggregation of ZIF-8 particles at particle loading higher than 15wt. %. Chemical analysis indicated an interaction between filler and polymer, and there were increases in the degree of crystallinity after the incorporation of ZIF-8.